Analysis of Dietary Patterns and Their Relationship With Body Mass Index (BMI) Among 2022 Medical Students At UNPRI - Jaya Harta Winata; Edy Fachrial; Wienaldi Wienaldi (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Dietary patterns strongly influence Body Mass Index (BMI), a key anthropometric measure for nutritional status. Medical students face dietary disruptions from academic stress and irregular schedules, increasing obesity risk. Objective: To examine the association between dietary patterns and BMI among Universitas Prima Indonesia medical students, class of 2022. Methods: A quantitative correlational cross-sectional study was conducted on 198 randomly sampled students. A 15-item dietary pattern questionnaire (Cronbach's α = 0.959) and measured weight and height data were used. Data were analyzed with univariate statistics, the Kolmogorov–Smirnov normality test, and Spearman correlation. Results: Fifty-one percent of students had good dietary patterns, while 61.1% exhibited non-normal BMI (overweight or obese). Spearman analysis showed a strong negative correlation between dietary patterns and BMI (r = –0.639, p < 0.001). Conclusion: Better dietary patterns are significantly associated with normal BMI. Interventions promoting healthy eating and continued nutritional education are recommended.